Preoperative assessment of stapes implantations of the vibrant SoundBridge for congenital aural atresia patients. (2nd September 2017) - Wang, Danni; Han, Demin; Zhao, Shouqin; Ren, Ran; Dong, Jiyong
Abstract: Objective: The objective of this study is to retrospectively analyze the imaging characteristics of patients with congenital aural atresia who underwent Vibrant Soundbridge implantation, and to investigate the importance of preoperative evaluation of vibroplasty. Materials and methods: The study included 16 patients with bilateral congenital aural atresia aged 6–25 years (mean age, 14.7 years). All patients underwent Vibrant Soundbridge implantations. Results: Among the 16 patients, 15 successfully underwent stapes implantation. The average height of the stapes of these 15 patients was 2.93 mm, which was significantly different from that of the control group with normal hearing ( p ≤ .001). The average distance between the tympanic segment of the facial nerve and the stapes was 1.41 mm in patients in whom the oval window was occluded by the displaced facial nerve. In the non-occluded group, the average distance was 2.00 mm. No significant difference was observed between the two groups ( p = .08). Conclusion: The distance between the facial nerve and stapes, as well as the height of the stapes, could be important predictors of successful stapes implantation of Vibrant Soundbridge.